Electroacupuncture Improves Baroreflex and γ-Aminobutyric Acid Type B Receptor-Mediated Responses in the Nucleus Tractus Solitarii of Hypertensive Rats - Qi Zhang; Ying-Ying Tan; Xiao-hua Liu; Fan-Rong Yao; Dong-Yuan Cao (Neural Plasticity)
Electroacupuncture (EA) has been reported to benefit hypertension, but the underlying mechanisms are still unclear. We hypothesized that EA attenuates hypertension, in part, through modulation of γ-aminobutyric acid (GABA) receptor function in the nucleus tractus solitarii (NTS). In the present study, the long-term effect of EA on GABA receptor function and expression was examined in the NTS of two-kidney, one-clip (2K1C) renovascular hypertensive rats. EA (0.1–0.4 mA, 2 and 15 Hz) was applied at Zusanli (ST36) acupoints overlying the deep fibular nerve for 30 min once a day for two weeks. The results showed that long-term EA treatment improved blood pressure (BP) and markedly restored the baroreflex response in 2K1C hypertensive rats. The increased pressor and depressor responses to microinjection of GABAB receptor agonist and antagonist into the NTS in the hypertensive rats were blunted by the EA treatment. Moreover, EA treatment attenuated the increased GABAB receptor expression in the NTS of hypertensive rats. In contrast, EA had no significant effect on the GABAA receptor function and expression in the NTS of 2K1C hypertensive rats. These findings suggest that the beneficial effects of EA on renovascular hypertension may be through modulation of functional GABAB receptors in the NTS.